Active noise control of higher modes in a duct using near field compensation and a ring of harmonic acoustic pneumatic sources. (January 2022) - Drant, Julien; Micheau, Philippe; Berry, Alain
Highlights: Active noise control method developed for the reduction of the radiated sound power of turbofans by using harmonic acoustic pneumatic sources (HAPS) developed inside the laboratory. Use of a duct geometry to simplify the multimodal propagation modeling. Control strategy by compensation based on a preliminary learning step based resulting from the direct minimization of the radiated sound power. Numerical studies allow the validation of this control strategy and the analysis of the active compensation mechanisms. Sound power attenuations larger than 20 dB are measured on an experimental test bench using a ring of 6 near-field microphones. Abstract: The motivation of this work was to develop an efficient method of tonal active control of the sound power radiated by turbofans. To develop and validate a concept with a multimodal propagation model, the simplified geometry of a duct cylinder is considered for the problem statement. Two design constraints are imposed: i) an array of Harmonic Acoustic Pneumatic Source (HAPS) must be used as secondary sources instead of loudspeakers ii) an array of error microphones must be implemented close to the exhaust and secondary sources. The requirement of error microphones in the near-field of control sources leads to an original theoretical multivariable control strategy by compensation. It is practically implemented with a preliminary learning step based on the measurement of the optimal control inputs and the residual sound field at the near-field microphones resulting from the direct minimization of the radiated sound power. Numerical studies allow the validation of this control strategy and the analysis of the active compensation mechanisms. A dedicated controller is designed to provide highly accurate magnitude and phase of the HAPS acoustic response. Sound power attenuations larger than 20 dB are measured on an experimental test bench using a ring of 6 HAPS and a ring of 6 near-field microphones in situations where the primary sound power is up to 130 dB-SWL. All the experimental results are consistent with the numerical analysis of the compensation matrix.